Platelet and Coagulation Function in Patients with Abnormal Cardiac Valves Treated with Sulphinpyrazone - Ludlam, C A; Allan, N; blandford, R B; Dowdle, R; Bentley, N J; Bloom, A L (Thrombosis and Haemostasis, 1981)
Eight patients on warfarin with rheumatic heart disease and prosthetic cardiac valves were selected for study on the basis of persistently elevated plasma β-thromboglobulin (β-tg) and platelet factor 4 (PF4) concentrations. Platelet mean lifespan and fibrinogen half life were short, and positively correlated, and both were inversely related to the Plasma concentrations of the platelet specific proteins. Antithrombin III (ATIII) levels were also reduced. Treatment with sulphinpyrazone resulted in lengthening of both platelet and fibrinogen survival, a rise in ATIII but no change in the βtg or PF4 concentrations. It is concluded that patients with abnormal cardiac valves and raised plasma levels of βtg or PF4 have, despite warfarin, a consumption coagulopathy that can be inhibited by sulphinpyrazone.
Keywords: Abnormal cardiac valves; β-thromboglobulin; Platelet factor 4; Platelet survival; Fibrinogen survival; Antithrombin III; Sulphinpyrazone